2002
DOI: 10.1589/rika.17.199
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relationship between Toe and Dynamic Postural Control.

Abstract: The purposes of this study were to examine the roles of toe in dynamic postural control during horizontal and vertical movements, and to elucidate the relationship between dynamic postural control and toe grasp power in healthy young subjects. Three kinds of non-weight bearing insoles, that without weight on a great toe, that without weight on the second to fifth toes, and that without weight on all toes, and an insole of weight bearing were prepared. Center of foot pressure was measured during forward functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…In cases of floating toe, the force maintaining toe pressure weakens. This does not influence the static balance greatly, but it does influence the dynamic balance significantly, and it is also related to the length of stride and walking speed [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…In cases of floating toe, the force maintaining toe pressure weakens. This does not influence the static balance greatly, but it does influence the dynamic balance significantly, and it is also related to the length of stride and walking speed [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Copyright © 2018 The Japanese Association of Rehabilitation Medicine al., [10][11][12][13][14] there is significant correlation between the reaching distance of the arm and the toe grip strength in forward reaching movements. Schlenstedt et al 15) reported that the distance of the COP shift in the front-back direction decreased significantly after single-leg balance exercise.…”
Section: Effects Of Reach Balance Exercise On Toe Grip Strength and Bmentioning
confidence: 99%
“…Correlation has been observed between the forward reaching distance of the arm and the toe grip strength. [10][11][12][13][14] In RB-T, which requires posture control on a single leg to avoid falling, it is necessary to reach out the arm and the leg while always controlling the COP position within the base of support of the foot. It is considered that repeatedly performing this motion is effective for improving the neurogenic muscle strength of toe flexors.…”
mentioning
confidence: 99%
“…Soma et al 5 ) indicated the relationship between TGS increase and the Functional Reach Test; maximum step length; and improvement in walking ability. In recent years, there have been several studies on TGS 6 , 7 , 8 , 9 , 10 ) . However, most of these were conducted involving healthy adults and the elderly, and there have been few reports of TGS in athletes.…”
Section: Introductionmentioning
confidence: 99%